2018
DOI: 10.3389/fphys.2018.00221
|View full text |Cite
|
Sign up to set email alerts
|

A Rhodopsin-Like Gene May Be Associated With the Light-Sensitivity of Adult Pacific Oyster Crassostrea gigas

Abstract: Light-sensitivity is important for mollusc survival, as it plays a vital role in reproduction and predator avoidance. Light-sensitivity has been demonstrated in the adult Pacific oyster Crassostrea gigas, but the genes associated with light-sensitivity remain unclear. In the present study, we designed experiments to identify the genes associated with light-sensitivity in adult oysters. First, we assessed the Pacific oyster genome and identified 368 genes annotated with the terms associated with light-sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Tidal expression of Cghiomt may shape the temporal action of melatonin in a tidal manner. Similarly, a tidal rhythmicity of the Cgrhodopsin-likes 1-3, which are homologues of the rhodopsin involved in light signal transduction [32], is observed. One can be argued that this tidal rhythmicity is explained by a tidal periodicity of light availability to the gills inside the palleal cavity, as a result of the valve opening tidal rhythm.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Tidal expression of Cghiomt may shape the temporal action of melatonin in a tidal manner. Similarly, a tidal rhythmicity of the Cgrhodopsin-likes 1-3, which are homologues of the rhodopsin involved in light signal transduction [32], is observed. One can be argued that this tidal rhythmicity is explained by a tidal periodicity of light availability to the gills inside the palleal cavity, as a result of the valve opening tidal rhythm.…”
Section: Discussionmentioning
confidence: 80%
“…To investigate the expression of the circadian clock genes in the field, oysters were collected at the same location as for the behavioural study (figure 3 [31], and three rhodopsin-likes genes (Cgrhodopsin-like 1, 2, 3) are known to be associated with light perception [32]. The statistical analysis (figure 3c) using the RAIN algorithm [28] indicated a significant tidal rhythm for five circadian clock genes: Cgclock, Cgbmal1, Cgtim1, Cgror and Cgrev-erb, which peaked during high tide slack.…”
Section: (C) Tidal Expression Of Circadian Clock Genes In the Fieldmentioning
confidence: 99%
“…The promotion of red light on eyespot larvae settling was also proposed in the study of C. gigas (Kim et al, 2021). Recently, four rhodopsin-like superfamily genes were identified in the genomic study of C. gigas (Wu et al, 2018), which provided us with another perspective on it.…”
Section: Resultsmentioning
confidence: 91%
“…It was further found that gene duplications via retroposition produce intronless opsins (which may be a general feature of G‐protein‐coupled receptors; Brosius, 1999) probably for enhancement of transcription efficiency and generation of new opsin variants by modifications at functional sites may broaden the spectral sensitivity of scallop eyes (Li et al, 2017). It was found that even in the bivalve mollusc without noticeable eyes, vision‐related genes are largely preserved in the genome and such preservation may confer the light‐sensitivity capacity of the animal as validated by an RNA interference experiment (Wu et al, 2018).…”
Section: Eye Origin and Evolutionmentioning
confidence: 99%